Coping with Knowledge Conditions: A Reply to Reviewers - Patrik Aspers (Sociologica)
This reply to the three reviews serves three purposes: it briefly recapitulates the core points of the book, addresses the specific comments raised by the reviewers, and provides general, forward-looking reflections on research in this field. For each comment raised, the responses offer elaborations and extensions, connecting the discussion to broader questions such as knowledge, truth, and the interplay between subjective and objective uncertainty.